Fatty acid-binding proteins: functional understanding and diagnostic implications. Issue 6 (November 2019) - Xu, Heli; Diolintzi, Anastasia; Storch, Judith
Abstract : Purpose of review: Fatty acid-binding proteins (FABPs) are a family of small, abundant proteins with highly tissue-specific expression patterns whose different functions remain incompletely understood. The purpose of this review is to summarize recent findings regarding FABP functions and mechanisms of action, including their potential utilization as serum markers of tissue-specific metabolic diseases. Recent findings: FABPs are important not only in their tissues of origin but also appear to influence the metabolism and function of tissues distal to their sites of expression. This may be secondary to metabolic changes in their primary tissues, and/or a result of FABP secretion from these tissues leading to effects on distal sites. Their levels in the circulation are increasingly explored as potential biomarkers for tissue-specific disease prognosis and progression. Summary: The nine fatty acid-binding members of the FABP family have unique tissue-specific functions and important secondary effects on tissues in which they are not expressed. For many of the FABPs, circulating levels may be indicative of disease processes related to their primary tissues, and may influence physiological function in distal tissues.